Trabalho e costume de feirantes de alimentos: pequenos comerciantes e regulamentações do mercado em Feira de Santana (1960/1990) - Pacheco, Larissa Penelu Bitencourt (2009)
The following text deals with the behavior of the small food traders in Feira de Santana, facing the transformations of the Free Market in the city, between 1960 and 1990. In these thirty years of history, this text selected the sale and use practices of the city center for itinerant trade of fruits, vegetables and products, an element that characterized the participation of these people in that shopping plaza, in order to understand how their social relationships were locked in conflict or negotiation with public policies proposed to the supply market and then how they reacted in face of the changes. The policy that brought some elements opposed to all this learning, especially the construction of the Centro de Abastecimento in Feira de Santana, showed changes in the relationship between trade and the city center and reached the behavior of the small traders. The intervention was felt in different ways among the subjects of the fair. We will seek to understand continuities and updates of the traditional buying and selling relationships between wholesalers and retailers in the region. The meanings of work at the fair are taken as core to the diversity experience debate shared with the open market and the peculiar characteristics of those vendors who come from the countryside to the city. The research sources are minutes of the City Council, City Hall documents (executive acts), official publications of the executive in the press, registration of tax payers, small traders testimonials, photos, press, minutes of the small traders association, poems and literary texts, demonstrating an attempt to meet with a social history of the free fair in the construction environment of regulatory codes, which culminated in the official withdrawal of the fair from the city center.